Pre- and postpartum employment patterns: comparing leave policy reform in Canada and Switzerland. Issue 3 (27th May 2022) - Antonini, Matteo; Pullman, Ashley; Fuller, Sylvia; Andres, Lesley
ABSTRACT: In recent decades, many countries modified their maternity and parental leave programmes, changing elements such as length, wage replacement levels, and eligibility criteria. We employ sequence analysis of women and men's employment trajectories in the two years before and after a birth to explore changes occurring alongside reforms that advanced different policies: a short, compulsory, and well-compensated maternity leave in Switzerland in 2005, and a long, voluntary, but less well-compensated parental leave in Canada in 2001. Our results show that employment patterns changed little after the reform in Switzerland. Most Swiss women remained in or switched to part-time employment in the period preceding childbirth. After the reform in Canada, mothers in the province of British Columbia—the context of our study—spent more time out of employment after the birth of a child. However, they were also more likely to return to work full time. In both contexts, the employment trajectories of men did not change. Together the results highlight that parents are not passive recipients of policy change; rather, reform may reinforce old patterns or generate change depending on the extent of change and the context where it takes place.